Proximal aperture in Cephalanthera longifolia (L.) Fritsch (Orchidaceae) pollen: a rare germination site for angiosperms - Carola Purgina; Friðgeir Grímsson; Silvia Ulrich (Botanical Studies)
Abstract The pollen dispersal unit of the epidendroid species, Cephalanthera longifolia, is a soft pollinium consisting of loosely connected tetrads that are agglutinated by elastoviscin. With scanning electron microscopy, the reticulate exine is visible on the outer pollen grains of outer tetrads of a pollinium. The pollen grains are mostly arranged in planar-tetragonal tetrads or decussate tetrads and easily disintegrate into monads. Contrary to the inaperturate pollen in members of subfamily Epidendroideae known so far, C. longifolia exhibits ulcerate pollen. When pollen grains are attached in tetrads within a pollinium the apertures are obscured, as they are located on the proximal side of the pollen grains. The ulcus can only be observed when tetrads disintegrate, freeing the monads and exposing the proximal side of pollen grains for investigation by light and scanning electron microscopy. Proximal aperture configurations are rare among angiosperms and currently known only from few other species of flowering plants. This is the first report of an ulcerate proximal aperture within Orchidaceae.